SISTEM PENDUKUNG KEPUTUSAN SELEKSI PENERIMAAN BANTUAN PROGRAM SEMBAKO MENGGUNAKAN METODE SMART (SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE) (STUDI KASUS : DINAS SOSIAL KOTA BINJAI) - Nur Aprilia Rahayu; Budi Serasi Ginting; Magdalena Simanjuntak (STMIK KAPUTAMA, 2021)
With the existence of policies provided by the government, especially in the field of Empowerment and Social Security in terms of providing basic food assistance programs for the underprivileged, it is necessary to determine who is eligible to receive this assistance. This assistance is given to underprivileged people to help meet their needs to improve their welfare. To help determine the selection of basic food assistance programs that receive the assistance, a Decision Support System (SPK) is needed. The method used in this research is the Simple Attribute Rating Technique (SMART) method. This method is a method that is often used to select several problems in the form of ranking. This method was chosen because the computation system is simple and easy to understand. From the results of the calculations that have been done, the ranking results with the highest value are Zuraida (A5) with a value of 0.8 and a percentage of the final value of 16.41% which is very suitable to receive non-cash assistance.